2020
DOI: 10.1007/s00464-020-08119-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on an interdisciplinary endoscopy unit in a German “hotspot” area: a single center experience

Abstract: Background and study aims Since December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative pathogen of coronavirus disease 2019 (COVID-19), has posed a pandemic threat to global health and has challenged health care system in all affected countries. Patients and methods This is a combined study including a descriptive part about the changes in the daily work routine of an Interdisciplinary Endoscopic Unit (IEU) and a prospective analysis of patients tested positive for SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Fifteen studies with a total of 122 COVID-positive patients reported the potential COVID-19 transmission rate, as shown in Table 2 . 11 , 19 , 20 , 22 24 , 26 34 Three studies 11 , 19 , 32 reported potential transmission of SARS-CoV-2 within GI endoscopy units, for a total of 46 HCWs or patients. The total basic reproduction rate (R0) equals 0.37, while the subgroup results from Asia, Europe, and America are 0.13, 0.44, and 0.33, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen studies with a total of 122 COVID-positive patients reported the potential COVID-19 transmission rate, as shown in Table 2 . 11 , 19 , 20 , 22 24 , 26 34 Three studies 11 , 19 , 32 reported potential transmission of SARS-CoV-2 within GI endoscopy units, for a total of 46 HCWs or patients. The total basic reproduction rate (R0) equals 0.37, while the subgroup results from Asia, Europe, and America are 0.13, 0.44, and 0.33, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of PPE use on the transmission of SARS-CoV-2 within GI endoscopy units is evaluated by comparing the differences of PPE use between the studies that reported no transmission and the studies that reported positive transmissions. Eight studies 20 , 27 , 29 34 were finally included for the analysis of PPE use in GI endoscopy units. Seven studies 20 , 27 , 29 31 , 33 , 34 claimed that no transmission of SARS-CoV-2 was found in their GI endoscopy unit, whereas one study 32 demonstrated successful screening of 3 COVID-positive transmitted cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations